Implementasi Metode Inisiasi dalam Mencegah Terjadinya Kredit Macet di Bank Muamalat KCP Ponorogo - Aisi, Okta Husna; Iwan Ridhwani; Alfian Jhohari, Nur (Lembaga Penerbitan dan Publikasi Ilmiah, 2025)
Bad credit is a condition where a borrower or so-called debtor does not fulfill his obligations in paying debts or principal installments according to the schedule or tempo determined according to the initial agreement. This condition often occurs due to various factors, including a decline in the debtor's financial capacity, unstable economic conditions, and less than optimal financial management. In the banking sector, bad credit or Non-Performing Loans (NPL) can have a serious impact on the liquidity and profitability of financial institutions, as well as disrupt the stability of the financial system as a whole. Efforts to overcome bad credit include loan restructuring, improving risk management, and strict supervision of credit disbursement. This can be done through the initiation method, namely a series of processes and procedures designed to assess and validate potential customers before providing access to banking services or products. This method is carried out to ensure that only customers who meet the criteria are allowed to start a business relationship with the bank, whether for the purposes of opening an account, providing credit or using other financial products. The initiation method used by Bank Muamalat Ponorogo is by solicitation (excavating in-depth information, evaluation (assessment) and approval). This method can be a solution to prevent bad credit which is often faced by financial institutions (banking).